Kondisi sosial ekonomi masyarakat di desa wisata budaya Pasar Keramat - Dzikrullooh, Rahmania Ramadhani; Islamudin, Mohamad Mujahid (Maliki Interdisciplinary Journal, 2024)
Kramatjetak Hamlet is a cultural and culinary tourism village located in Warugunung Village, Pacet Subdistrict, Mojokerto Regency, East Java. Unlike other villages in general, Kramajetak Hamlet has its own attraction for the local community because the village has its own characteristics and uniqueness, namely through the development and empowerment of the local community to advance the village. This research aims to explore deeper information related to the role of the community and socio-economic conditions in developing the cultural and culinary tourism village of Pasar Keramat. This research uses a qualitative method with a descriptive analysis approach. Collecting data and information at the research location by conducting observations, and interviews. The data analysis technique used is data reduction, data presentation and drawing conclusions. The results of this study indicate that the people of Kramajetak hamlet are able to make the potential of residents in their area into something of positive value, through the Keramat market as a cultural and culinary tourism can increase the role of the community and the participation of residents of Kramajetak hamlet in developing the Keramat market performance and provide benefits to the socio-economic conditions of the local village community.